Check list of jumping plant-lice (Hemiptera: Psylloidea) of the Korean Peninsula - Cho, Geonho; Burckhardt, Daniel; Lee, Seunghwan (Zootaxa, 2022)
An updated check list of Psylloidea from the Korean Peninsula is provided with information on the distribution of each species within the Peninsula and host plants based on published records and our own extensive field surveys. Five species (Calophya phellodendri Loginova, Calophya rhopenjabensis Li, Cacopsylla initialis (Loginova), Cacopsylla sibirica (Loginova) and Cacopsylla viburnicola (Li & Yang)) are reported for the first time from Korea, bringing the number to 130 species in 32 genera and six families. Three generic and subgeneric names are synonymised: Bactericera Puton, 1876 = Spinotrioza Kwon & Kwon, 2020, syn. nov.; Cacopsylla Ossiannisson, 1970 = Psylla (Koreopsylla) Kwon & Kwon, 2020, syn. nov. = Cacopsylla (Megapteripsylla) Kwon & Kwon, 2020, syn. nov. Three genera of Triozidae are redefined, viz. Dyspersa Klimaszewsi, 1968, Spanioza Enderlein, 1926 and Trichochermes Kirkaldy, 1904. Sixteen nominal species are synonymised: Celtisaspis japonica (Miyatake, 1968), nomen protectum = Arytaina cornicola Frauenfeld, 1869, nomen oblitum, syn. nov. = Celtisaspis guizhouana Yang & Li, 1982, syn. nov. = Celtisaspis sinica Yang & Li, 1982, syn. nov. = Celtisaspis zhejiangana Yang & Li, 1982, syn. nov.; Celtisaspis usubai (Miyatake, 1980) = Celtisaspis beijingana Yang & Li, 1982, syn. nov.; Calophya rhopenjabensis Li, 2011 = Calophya elaeocarpae Li, 2011, syn. nov.; Calophya verticornis Kwon, 1983 = Calophya melanocephala Li, 1997, syn. nov.; Cacopsylla araliae (Konovalova, 1981) = Cacopsylla (Hepatopsylla) aralicola Kwon & Kwon, 2020, syn. nov.; Cacopsylla diaphana (Konovalova, 1981) = Psylla (Cacopsylla) peninsularis Kwon, 1983, syn. nov.; Cacopsylla moiwasana (Kuwayama, 1908) = Psylla micromeli Konovalova, 1981, syn. nov.; Cacopsylla nigella (Konovalova, 1979) = Psylla liaoli Yang & Li, 1981, syn. nov. = Psylla sandolbaea Park & Lee, 1982, syn. nov.; Livia jesoensis Matsumura, 1908 = Livia baegunsana Kwon & Kwon, 2020, syn. nov.; Trichochermes grandis Loginova, 1965 = Trichochermes gemellus Loginova, 1974, syn. nov.; Trichochermes rhamnisugus (Li, 1994) = Trioza naria Kwon, Suh, An & Huh, 1996, syn. nov.; Trioza quercicola Shinji, 1944 = Dyspersa hambaeksana Kwon & Kwon, 2020, syn. nov. Five species are removed from synonymy: Cacopsylla cyphospila Li, 2011, stat. rev.; Cacopsylla fluctimaculata Li, 2005, stat. rev.; Cacopsylla gossypinmaculosa Li, 2011, stat. rev.; Cacopsylla nigrigenimacula Li, 2011, stat. rev.; Trioza chilgia Park & Lee, 1980, stat. rev. Twenty five new combinations are proposed: Cacopsylla diaphana (Konovalova), comb. nov., Cacopsylla initialis (Loginova), comb. nov., Cacopsylla sibirica (Loginova), comb. nov., Cacopsylla silvestris (Bajeva), comb. nov.; all from Psylla; Dyspersa abdominalis (Flor), comb. nov.; Dyspersa achilleae (Wagner), comb. nov.; Dyspersa agrophila (Löw), comb. nov.; Dyspersa carpathica (Dobreanu & Manolache), comb. nov.; Dyspersa chrysanthemi (Löw), comb. nov.; Dyspersa cirsii (Löw), comb. nov.; Dyspersa flixiana (Burckhardt & Lauterer), comb. nov.; Dyspersa kantshavelii (Gegechkori), comb. nov.; Dyspersa liberta (Loginova), comb. nov.; Dyspersa mica (Loginova), comb. nov.; Dyspersa munda (Foerster), comb. nov.; Dyspersa schrankii (Flor), comb. nov.; Dyspersa senecionis (Scopoli), comb. nov.; Dyspersa stugma (Tuthill, 1939), comb. nov.; Dyspersa viridula (Zetterstedt), comb. nov.; Spanioza cocquempoti (Burckhardt & Lauterer), comb. nov., Spanioza drosopouli (Burckhardt & Lauterer), comb. nov.; Trichochermes marginepunctatus (Flor), comb. nov.; Trichochermes rhamni (Schrank), comb. nov.; all from Trioza; Triochochermes rhamnisugus Li, comb. nov. from Triozopsis; Trioza jejuensis (Kwon & Kwon), comb. nov. from Dyspersa. Twelve previous combinations are reinstated: Bactericera calcarata (Schaefer), comb. rev. from Spinotrioza; Cacopsylla moiwasana (Kuwayama), comb. rev. from Acizzia; Dyspersa laserpitii (Burckhardt & Lauterer), comb. rev.; D. lautereriella (Burckhardt), comb. rev.; D. mesembrina (Burckhardt), comb. rev.; D. pallida (Haupt), comb. rev.; all from Trioza; Togepsylla matsumurana Kuwayama, comb. rev. from Hemipteripsylla; Trioza camphorae Sasaki, comb. rev.; T. cinnamomi Boselli, comb. rev.; T. machilicola Miyatake, comb. rev.; T. quercicola Shinji, comb. rev.; T. usubai Matsumoto, comb. rev.; all from Dyspersa. One new replacement name, Cacopsylla kwonorum Cho & Burckhardt, nom. nov., is proposed for Cacopsylla silvestris (Kwon, 1983), nec Cacopsylla silvestris (Bajeva, 1969). Comments are provided for some species.